Wound healing of experimental equine skin wounds and concurrent microbiota in wound dressings following topical propylene glycol gel treatment - Labens, Raphael; Raidal, Sharanne; Borgen-Nielsen, Cathrine; Pyecroft, Stephen; Pant, Sameer D.; De Ridder, Thomas (Frontiers in Veterinary Science, 2023)
Topical wound treatments rely on carrier formulations with little to no biological impact. The potential for a common vehicle, a propylene glycol (PG) gel, to affect wound healing measures including microbiota is not known. Microbiome characterization, based on next generation sequencing methods is typically performed on tissue or directly obtained wound fluid samples. The utility for primary wound dressings to characterize equine wound microbiota in the context of topical treatments is currently unknown. This investigation reports the topical effect of an 80% PG based gel on wound healing and microbiota in wound dressings. Experiments utilized an equine distal limb wound model, histology of sequential wound biopsies, photographic wound measurements and microbiota profiling via 16s rRNA sequencing of dressing samples. While clinical outcomes 42 days post wounding were similar irrespective of PG gel exposure, treatment delayed a natural decline of polymorphonucleated cells in wounds, slowed initial wound healing, increased microbial diversity in terms of operational taxonomic units (OTU) and affected alpha-diversity in primary wound dressings. Relative abundances of OTUs were similar to those previously reported for equine wounds. Results highlight the potential for vehicle exposure to alter relevant wound outcome measures imposing the need for stringent experimental control measures. Primary wound dressings may represent an alternate sample source for characterization of the wound microbiome alleviating the need for additional interventions. Further studies are warranted to contrast the microbiome in wound dressings against that present on wound surfaces to conclude on the validity of this approach.